Spatial analysis of groundwater quality and potential for irrigation using hydrogeological and water quality parameters: insights from Bargarh Canal command area - Mohapatra, Priyanka; Paul, Jagadish Chandra; Das, Dwarika Mohan; Sahu, Ambika Prasad; Raul, Sanjay Kumar; Singh, Laishram Kanta; Devi, Sougrakpam Roma; Singha, Arun Kumar; Mohanty, Amulya Kumar (Frontiers in Water, 2026)
An efficient groundwater management strategy requires identification of groundwater potential zones with a good groundwater quality index. The present study uses analytic hierarchy procedure (AHP) to identify potential groundwater resource zones along with quality for irrigation purposes in the Bargarh Canal command area of Odisha, India. The groundwater potential zone (GWPZ) was assessed using the geology, lineament density, geomorphology, groundwater fluctuation, soil type, topographic wetness index (TWI), slope, canal density, drainage density, and land use/cover of the study area. The groundwater quality index (GWQI) considers seven indices viz. sodium adsorption ratio (SAR), sodium percentage (Na%), magnesium hazard (MH), permeability index (PI), residual sodium carbonate (RSC), Kelly's ratio (KR), soluble sodium percentage (SSP) and three chemical parameters like electrical conductivity, chlorine, nitrate. The study area was categorized into three groundwater potential zones with 71.8% accuracy: good (48.12%), moderate (41.72%), and poor (10.16%). Irrigation water quality was assessed using Piper, United States Salinity Laboratory (USSL), and Wilcox Diagrams. Utilizing the groundwater quality index, the study region was divided into three distinct groundwater quality zones with an accuracy of 73.6%: poor (4.02%), moderate (45.20%), and good (50.78%). This classification was achieved through receiver operating characteristic (ROC) and area under curve (AUC) analyses, which demonstrated strong model reliability. Superimposition of the GWQI map over the GWPZ map reveals some degree of overlap between good potential zones with poor quality, which can guide policymakers and water managers for groundwater resource management and planning, underscoring the importance of both quantity and quality aspects.